1996
DOI: 10.1111/j.1432-1033.1996.0093t.x
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Mechanisms Governing Tumor‐Necrosis‐Factor‐Mediated Regulation of Plasminogen‐Activator Inhibitor Type‐2 Gene Expression

Abstract: Plasminogen-activator inhibitor type 2 (PAI-2), a serine protease inhibitor involved in the regulation of urokinase-dependent proteolysis, is also implicated in the inhibition of tumor-necrosis-factor-(TNF)-mediated apoptosis. The PAI-2 gene is one of the most TNF-responsive genes known and is also highly induced by the phorbol ester phorbol 12-myristate 13-acetate (PMA) and the phosphatase inhibitor, okadaic acid, in both HT-1080 fibrosarcoma and U-937 histiocytic cells. We sought to identify and characterize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
20
0
2

Year Published

1999
1999
2011
2011

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 27 publications
3
20
0
2
Order By: Relevance
“…Notwithstanding the important contribution of transcriptional control of PAI-2 expression (13,14), the role of posttranscriptional regulation of the PAI-2 gene has recently been highlighted (1,15). These investigations stemmed from earlier results whereby treatment of HT-1080 fibrosarcoma cells with a combination of PMA and TNF produced a 50 -100-fold increase in PAI-2 gene transcription but a 1500-fold increase in PAI-2 mRNA over a 24-h period (9).…”
mentioning
confidence: 67%
See 3 more Smart Citations
“…Notwithstanding the important contribution of transcriptional control of PAI-2 expression (13,14), the role of posttranscriptional regulation of the PAI-2 gene has recently been highlighted (1,15). These investigations stemmed from earlier results whereby treatment of HT-1080 fibrosarcoma cells with a combination of PMA and TNF produced a 50 -100-fold increase in PAI-2 gene transcription but a 1500-fold increase in PAI-2 mRNA over a 24-h period (9).…”
mentioning
confidence: 67%
“…Competition experiments confirmed that the two fastest migrating complexes (referred to as complexes I and II) were specific as only the unlabeled 4A RNA sequence competed for binding (lanes 3-5). Binding was not competed by cold RNA sequences harboring the 4B and 4C region of exon 4 (lanes 6 -11) or by RNA of unrelated (97-nt prothrombin 3Ј-UTR) sequence (lanes [12][13][14]. No specific binding of cytoplasmic proteins was observed to either the 4B or 4C probes (data not shown).…”
Section: Mrna Instability Elements Within the Coding Region Of Pai-2 mentioning
confidence: 99%
See 2 more Smart Citations
“…PAI-3 regulates enzymes involved in fertilization rather than lung tissue fibrosis, whereas altered expression of both PAI-1 and PAI-2 is of potential relevance to the process of lung fibrosis (24,25). Although PAI-2 exhibits inhibitory activity toward tPA and uPA (26,27), the efficiency of PAI-2 is 20-to 100-fold less than what is observed for PAI-1 (28). PAI-2 is not generally detectable in human plasma, except during pregnancy (29,30).…”
Section: Ast Cells Are Multifunctional Effector Cells That Partic-mentioning
confidence: 88%